Economic Aspects of Management of Tourist Space - Guzik, Halina; Ostrowska, Barbara (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The formation of contemporary world space in all its dimensions is dominated in large measure by humans. Tourism for regional and local economies as an economic factor in the formation of space is of increasing importance. Spatial phenomena occur in particular space, which they create, bringing about a particular form of usage, as well as shape and transform. The aim of the article is to show how space is formed by economic factors using the example of how tourist management influences tourist reception areas on a local basis. The analysis of indicators describing the function of tourism allows the author to assess the influence of tourism on economic development in the districts of Małopolska.